2008
DOI: 10.1002/chir.20541
|View full text |Cite
|
Sign up to set email alerts
|

Investigating by CD the molecular mechanism of elasticity of elastomeric proteins

Abstract: Elastomeric proteins are widespread in the animal kingdom, and their main function is to confer elasticity and resilience to organs and tissues. Besides common functional properties, elastomeric proteins share a common sequence design. They are usually constituted by repetitive sequences with a high content of glycine residues. From a conformational point of view, all the elastomeric proteins since now analyzed show a dynamic equilibria between folded (mainly beta-turns) and extended (polyproline II and beta-s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

10
81
0
1

Year Published

2010
2010
2018
2018

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(92 citation statements)
references
References 68 publications
10
81
0
1
Order By: Relevance
“…All sets of spectra exhibit strong minima at 195e200 nm and, consistent with previous studies of elastomeric proteins and peptides including tropoelastin and resilin (Bochicchio et al, 2008), there is a trend for these minima to decrease in intensity as temperature is increased (Fig. 5B).…”
Section: Circular Dichroism Studies Of Cf-resb and Hi-resbsupporting
confidence: 83%
“…All sets of spectra exhibit strong minima at 195e200 nm and, consistent with previous studies of elastomeric proteins and peptides including tropoelastin and resilin (Bochicchio et al, 2008), there is a trend for these minima to decrease in intensity as temperature is increased (Fig. 5B).…”
Section: Circular Dichroism Studies Of Cf-resb and Hi-resbsupporting
confidence: 83%
“…In contrast, resilin is thought to consist of unstructured domains and highly flexible poly-proline II structures moving in and out of a multiconformational equilibrium that acts as an entropic spring. When resilin is stretched, the resulting decrease in conformational entropy generates the restoring force with minimal energy loss (Bochicchio et al, 2008). The elastic recoil of abductin is thought to be driven in part by a similar mechanism as in resilin (Bochicchio et al, 2008), but also with a hydrophobic mechanism such that stretching the material reveals hydrophobic protein regions and the resting state returns to a conformation where the hydrophobic regions are sequestered from the aqueous environment (Tatham and Shewry, 2002).…”
Section: Evolution Of Elastic Mechanismsmentioning
confidence: 99%
“…When resilin is stretched, the resulting decrease in conformational entropy generates the restoring force with minimal energy loss (Bochicchio et al, 2008). The elastic recoil of abductin is thought to be driven in part by a similar mechanism as in resilin (Bochicchio et al, 2008), but also with a hydrophobic mechanism such that stretching the material reveals hydrophobic protein regions and the resting state returns to a conformation where the hydrophobic regions are sequestered from the aqueous environment (Tatham and Shewry, 2002). Thus, all of these materials rely on entropic forces to return to their resting state, but the underlying molecular arrangements and the use of hydrophibicity to mediate interactions with the surrounding medium in some systems, produce an impressive array of elastic material behaviors.…”
Section: Evolution Of Elastic Mechanismsmentioning
confidence: 99%
“…We demonstrated at molecular level, mainly by circular dichroism (CD), the existence of multiconformational equilibria among poly-L-proline II (PPII), b-turns, and unordered conformations. 5 At supramolecular level, we demonstrated that the polypeptide sequences encoded by the proline-rich domains are able to adopt the same behavior of the entire protein such as the coacervation. 6 Coacervation is an inverse phase-transition temperature-induced process that occurs at 378C for tropoelastin 7 and determines, at supramolecular level, the highly ordered filamentous organization of the protein.…”
Section: Introductionmentioning
confidence: 97%